Association between fluid balance and survival in critically ill patients. (27th June 2014) - Lee, J.; de Louw, E.; Niemi, M.; Nelson, R.; Mark, R. G.; Celi, L. A.; Mukamal, K. J.; Danziger, J.
Abstract: Objective: Although the consequences of chronic fluid retention are well known, those of iatrogenic fluid retention that occurs during critical illness have not been fully determined. Therefore, we investigated the association between fluid balance and survival in a cohort of almost 16 000 individuals who survived an intensive care unit (ICU) stay in a large, urban, tertiary medical centre. Design: Longitudinal analysis of fluid balance at ICU discharge and 90‐day post‐ICU survival. Measurements: Associations between fluid balance during the ICU stay, determined from the electronic bedside record, and survival were tested using Cox proportional hazard models adjusted for severity of critical illness. Results: There were 1827 deaths in the first 90 days after ICU discharge. Compared with the lowest quartile of discharge fluid balance [median (interquartile range) −1.5 (−3.1, −0.7) L], the highest quartile [7.6 (5.7, 10.8) L] was associated with a 35% [95% confidence interval (CI) 1.13–1.61)] higher adjusted risk of death. Fluid balance was not associated with outcome amongst individuals without congestive heart failure or renal dysfunction. Amongst patients with either comorbidity, however, fluid balance was strongly associated with outcome, with the highest quartile having a 55% (95% CI 1.24–1.95) higher adjusted risk of death than the lowest quartile. Isotonic fluid balance, defined as the difference between intravenous isotonic fluid administration and urine output, was similarly associated with 90‐day outcomes. Conclusion: Positive fluid balance at the time of ICU discharge is associated with increased risk of death, after adjusting for markers of illness severity and chronic medical conditions, particularly in patients with underlying heart or kidney disease. Restoration of euvolaemia prior to discharge may improve survival after acute illness.